APLIKASI MONITORING SISTEM ABSENSI SIDIK JARI SEBAGAI PENDUKUNG PEMBAYARAN BIAYA PEGAWAI TERPUSAT DENGAN SAP - Ageng Setiani Rafika; Mukti Budiarto; Wahyu Budianto (Universitas Raharja, 2015)
Monitoring Data on the presence of Usig Fingerprints is a strategic approach towards improving the discipline of employees, to achieve improved discipline such officials then needed an application monitoring system using Fingerprint time & attendance data are not effectively separated the human, infrastructure and overall management system for centralized employee fee payment process with SAP/ERP as expected and did not experience any delay in payment. Attendance System Monitoring application is capable of helping the PA (Payrool Administration) in favour of an increase in the accuracy of the data centralized employee fee payments with SAP can be realized should be supported by a reliable Technology Informatics infrastructure. Attendance Monitoring System application using the Fingerprint are created in this journal is an application programming examples that use the programming language visual basic 6.0 and SQL Server database, which is expected to help resolve problems existing in HUMAN RESOURCES in General and the ADM. Personnel in particular. The design of monitoring data on the presence of using fingerprints only handles input from someone who has been registered in the database, whereas the output that is displayed showing the reports relating to the attendance reports to be used as the supporter of the accuracy of the data centralized employee fee payments with SAP.